2014
DOI: 10.1161/jaha.113.000635
|View full text |Cite
|
Sign up to set email alerts
|

The American Heart Association Life's Simple 7 and Incident Cognitive Impairment: The REasons for Geographic And Racial Differences in Stroke (REGARDS) Study

Abstract: BackgroundLife's Simple 7 is a new metric based on modifiable health behaviors and factors that the American Heart Association uses to promote improvements to cardiovascular health (CVH). We hypothesized that better Life's Simple 7 scores are associated with lower incidence of cognitive impairment.Methods and ResultsFor this prospective cohort study, we included REasons for Geographic And Racial Differences in Stroke (REGARDS) participants aged 45+ who had normal global cognitive status at baseline and no hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
134
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 146 publications
(150 citation statements)
references
References 24 publications
12
134
3
1
Order By: Relevance
“…Numerous studies have established that higher numbers of ideal LS7 metrics or higher LS7 scores are strongly associated with favorable outcomes 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14. Our results are comparable to the findings of prior studies that have shown an inverse relationship between higher LS7 scores and the incidence of non‐CVD 15, 16, 17, 18, 19. In the ARIC study, Rasmussen‐Torvik et al demonstrated that participants with 6 or 7 ideal metrics had a 51% lower risk of cancer compared with those with 0 to 2 ideal metrics 15…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Numerous studies have established that higher numbers of ideal LS7 metrics or higher LS7 scores are strongly associated with favorable outcomes 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14. Our results are comparable to the findings of prior studies that have shown an inverse relationship between higher LS7 scores and the incidence of non‐CVD 15, 16, 17, 18, 19. In the ARIC study, Rasmussen‐Torvik et al demonstrated that participants with 6 or 7 ideal metrics had a 51% lower risk of cancer compared with those with 0 to 2 ideal metrics 15…”
Section: Discussionsupporting
confidence: 86%
“…The inverse relationship between ideal CVH and CVD incidence is well documented 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14. However, research exploring the association between ideal CVH and non‐CVDs has just begun 15, 16, 17, 18, 19…”
Section: Introductionmentioning
confidence: 99%
“…The prospective study design minimized the likelihood of reverse causality as an Our rich data set allowed for adjustment for many important measured confounders. Our definition of cognitive impairment captured a clinically relevant level of impairment and had face validity given the previously reported associations of risk factors with impairment [18,33], however we did not have evaluation for dementia or brain imaging, which are limitations of the study. Follow-up time was relatively short, which could be considered a weakness, but our large sample allowed accumulation of a large number of cases quickly with minimal attrition of participants.…”
mentioning
confidence: 99%
“…Participants were considered to have incident cognitive impairment if, over the course of the study, they had no cognitive impairment at the baseline 6-item screener and an impaired score on at least 2 of the other 3 tests during follow-up. 22 Requiring impaired scores in at least 2 of the tests was intended to further select for significant cognitive impairment. The mean follow-up time was 3.4 years.…”
mentioning
confidence: 99%